Journal of emerging market finance. (Sage, 2002)
The Journal of Emerging Market Finance is a forum for debate and discussion on the theory and practice of finance in emerging markets. While the emphasis is on articles that are of practical significance, the journal also covers theoretical and conceptual aspects relating to emerging financial markets.